Lysine Dendrigraft Nanocontainers. Influence of Topology on Their Size and Internal Structure - Boris Okrugin; Maxim Ilyash; Denis Markelov; Igor Neelov (MDPI AG, 2018)
Poly-l-ysine dendrigrafts are promising systems for biomedical applications due to their biodegradability, biocompatibility, and similarity to dendrimers. There are many papers about the use of dendrigrafts as nanocontainers for drug delivery. At the same time, the number of studies about their physical properties is limited, and computer simulations of dendrigrafts are almost absent. This paper presents the results of a systematic molecular dynamics simulation study of third-generation lysine dendrigrafts with different topologies. The size and internal structures of the dendrigrafts were calculated. We discovered that the size of dendrigrafts of the same molecular weight depends on their topology. The shape of all studied dendrigrafts is close to spherical. Density profile of dendrigrafts depends on their topology.